2018
DOI: 10.1097/md.0000000000012086
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum uric acid and arterial stiffness in a low-risk, middle-aged, large Korean population

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…Some studies have shown that sUA is related to markers of increased vascular damage, such as a low ABI (34) and higher sUA levels are associated with peripheral artery disease in the US general population (35). In our study, we found such association; accordingly, several studies reported that higher sUA was associated with a low ABI in women (36,37), potentially related to estrogen effects (38)(39)(40).…”
Section: Discussionsupporting
confidence: 67%
“…Some studies have shown that sUA is related to markers of increased vascular damage, such as a low ABI (34) and higher sUA levels are associated with peripheral artery disease in the US general population (35). In our study, we found such association; accordingly, several studies reported that higher sUA was associated with a low ABI in women (36,37), potentially related to estrogen effects (38)(39)(40).…”
Section: Discussionsupporting
confidence: 67%
“…The authors suggested that high UA may have unfavorable vascular effects even in low-risk populations, but they underlined the possible influence of the ethnic lifestyle on their results. 56 A previous Korean study conducted in asymptomatic healthy subjects with a mean age of 50.6 ±8.9 years who underwent a health examination failed to find any association between UA and arterial stiffness in women and men younger than 55 years. High-normal or greater UA levels were associated with an increased risk of arterial stiffness, measured as baPWV, in women older than 55 years, but not in men.…”
Section: Cross-sectional Studiesmentioning
confidence: 86%
“…These present results were in accordance with the recent case-control studies that focused on the causal relationship between uric acid and metabolic syndrome, and several cardiovascular diseases. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] However, conflicting results were still present. Parsa et al 21 reported that a decrease in serum uric acid has a causal effect of lowering blood pressure through the method of Mendelian randomization analysis in 516 Amish adults.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported the association between levels of circulating uric acid and arterial stiffness. 714 However, other studies did not find such relationship. 15,16 Observational studies have experienced residual problems of poorly measured or unmeasured confounding and reverse causality, when the disease process has a long latency period.…”
Section: Introductionmentioning
confidence: 90%